Socialization of Solutions to Overcome the Negative Impact of Gadgets on Teenagers in Ulu Gedong Village, Jambi City - Anggi, Esa; Munandar, Aris; Firmansyah, Joni; Harahap, Izhar; Saputra, Didi Hardi; Sodri, Ahmad; Asri, Asri; Arik, Al; Rosalinda, Mira; Andriani, Wina; Anjani, Rahma; Pitriani, Sri Rahmi; nurhikmah, nurhikmah; Lastari, Wahyuni Klara; Khoirunnisa, Khoirunnisa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Gadgets provide many conveniences, especially in the aspects of technology and information. However, gadgets also have a negative side, especially for children and teenagers. These negative impacts include deviant behavior such as fighting, brawling, theft, fraud and exposure to pornography. Excessive use of gadgets can also reduce the feeling of togetherness and mutual cooperation, replacing it with a selfish and individualistic nature due to too much time spent in cyberspace. Therefore, it is important for teenagers to be given education about how to deal with the negative effects of gadgets. This service aims to increase awareness of teenagers so that the negative impact of gadgets can be minimized, and the character of teenagers as the next generation of the Indonesian nation can be improved. The methods used in this activity include lectures, discussions and simulations. The number of participants was 35 people with an additional 3 presenters and 11 companions. From the results of this activity, it was found that participants gave a positive response, realizing that the negative impact of gadgets could damage the character of teenagers. Participants also hope that socialization activities like this can continue to be carried out as a reminder for future teenagers.